Strategi Guru dalam Pembentukan Kepribadian Sosial Siswa SMK di Kabupaten Pidie - Masykur Masykur (Tadabbur: Jurnal Peradaban Islam, 2021)
The study discusses the teachers’ concept in developing the students’ social characteristics at senior vocational schools (SMK) in Pidie District. The study used field research with qualitative approach, taking place at SMK Negeri 1 Sigli and SMK Mutiara. The subjects of the study included the school principals, administration staff, and teachers of Islamic education. Data were collected by interview and observation. The data were then analyzed through data reduction, data display, and conclusion drawing. The results of the study showed that the students’ social characteristics were developed by encouraging the students to have mutual respect and mutual care, to be confident, to perform good deeds, to interact socially, to remind one another, and to be responsible. These social characteristics were promoted through individual approach, the role of teachers as parents at school, improving communication, giving rewards, sanctions, and punishments, and cooperating with the parents. On the other hand, the problems in developing these characteristics included lack of religious education at home, poor living environment, unhealthy peer relationship, and limited lesson hours of Islamic education at school.